Wolf Stockburn, Railroad Detective: One Way to Boot Hill - Book 4 - O'Hara, Max (Thorndike, Maine : Center Point Large Print, 2023)
"Stretching across the wild western frontier, the railroad needs guardians like Wells Fargo detective Wolf Stockburn. Known as the Wolf of the Rails, the steely Scotsman is as cold and hard as the tracks he rides -- and those too foolish to fear him will soon lie dead at his feet . . . When train robbers hit the Boot Hill Express -- so called because of all the people riding it who have ended up dead -- with a full head of steam, Wolf Stockburn makes quick work of them. But the gun smoke has barely cleared when a second gang attacks, catching Stockburn by surprise. In a hail of hot lead he falls from the train and the thieves kill two guards and make off with the cattle the train was hauling. Now its a matter of honor and payback as he trails the outlaws -- his only clue a hoof print showing a faint star shape. Dodging a deadly bushwhacker, Stockburn, hell-on-wheels angry, teams up with a beautiful half- Comanche hellcat and follows a twisted trail of bullet- ridden corpses to a final reckoning in a Mexican ghost town -- where bad men end up dead . . . on the wrong side of the tracks."--
Keywords: Wells, Fargo & Company -- Employees; Fiction; Railroad police -- Fiction; Train robberies -- Fiction; Railroads -- Texas; Fiction; Western fiction